Positive electrode active material for lithium ion secondary battery, method for producing positive electrode active material for lithium ion secondary battery, and lithium ion secondary battery
By adjusting the chemical composition and particle characteristics of lithium metal composite oxide in the positive electrode active substance of lithium ion secondary battery, controlling the thickness and specific surface area of the oxygen-easy-emission layer, the problem of oxygen release under the charging state is solved and the thermal stability is improved .
Patent Information
- Application Number
- CN202411539378.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2019-02-26
- Filing Date
- 2020-02-26
- Publication Date
- 2025-02-11
AI Technical Summary
The problem of oxygen discharge in the charged state of the existing lithium-ion secondary battery positive electrode active material leads to a decrease in thermal stability.
The positive electrode active substance containing lithium metal composite oxide is adopted, and its chemical composition is the ratio of Li:Ni:Co:M=1+a:1-x-y:x:y. The oxygen is easy to charge at 4.3V by STEM-EELS analysis. The thickness of the discharge layer was controlled to be less than 200 nm, and the specific surface area was adjusted to be more than 0.7 m2/g and 2.0 m2/g.
It effectively suppresses oxygen emission in the charging state and improves the thermal stability of the positive electrode active material.
Smart Images

Figure BDA0005112407170000221 
Figure HDA0005112407180000011 
Figure HDA0005112407180000021
Abstract
Description
[0001] This application is a divisional application of the original application, with the application date of February 26, 2020, the application number 202080016275.8, and the invention name of "Positive electrode active material for lithium ion secondary battery, method for manufacturing positive electrode active material for lithium ion secondary battery, and lithium ion secondary battery". Technical Field
[0002] The present invention relates to a positive electrode active material for a lithium ion secondary battery, a method for producing a positive electrode active material for a lithium ion secondary battery, and a lithium ion secondary battery. Background Art
[0003] In recent years, along with the popularization of portable electronic devices such as portable phones and notebook personal computers, it is strongly desired to develop small and lightweight non-aqueous electrolyte secondary batteries with high energy density. In addition, as batteries for electric vehicles (xEV) such as electric vehicles, various hybrid vehicles, and fuel cell vehicles, it is strongly desired to develop secondary batteries with excellent capacity density.
[0004] As a secondary battery that meets such a requirement, there is a lithium ion secondary battery. A lithium ion secondary battery is composed of a negative electrode, a positive electrode, an electrolyte, etc., and a material capable of extracting and inserting lithium is used as the active material of the negative electrode and the positive electrode.
[0005] Such lithium ion secondary batteries are currently being actively researched and developed. Among them, lithium ion secondary batteries using layered or spinel lithium metal composite oxides as positive electrode materials can achieve a high voltage of 4V and are therefore being put into practical use as batteries with high energy density.
[0006] As the main materials proposed so far, there are lithium cobalt composite oxide (LiCoO2) which is relatively easy to synthesize, lithium nickel composite oxide (LiNiO2) which uses nickel which is cheaper than cobalt, and lithium nickel cobalt manganese composite oxide (LiNiO2). 1 / 3 Co 1 / 3 Mn 1 / 3 O2), lithium manganese composite oxide (LiMn2O4) using manganese, etc.
[0007] In order to obtain a lithium ion secondary battery with excellent energy density, it is necessary for the positive electrode active material to have a high charge and discharge capacity. Here, it is known that in order to increase the battery capacity, it is effective to increase the nickel (Ni) ratio of the positive electrode active material. Nickel has a low electrochemical potential compared to cobalt and manganese, which contributes to an increase in the change in the valence of the transition metal of charge and discharge, and an increase in charge and discharge capacity. However, if the nickel ratio is increased, as a negative effect, thermal stability is reduced. Therefore, a method for improving thermal stability has been studied, and it is known that a positive electrode material with high thermal stability, such as a lithium manganese composite oxide, is mixed with a lithium nickel composite oxide to ensure a method of thermal stability.
[0008] Patent Document 1 discloses a positive electrode active material obtained by mixing a nickel-lithium composite oxide and a lithium-manganese composite oxide having a predetermined composition at a mixing ratio (mass ratio) of 80:20 to 90:10.
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent Application Publication No. 2008-282667 Summary of the invention
[0012] Problems to be solved by the invention
[0013] However, in the method of mixing particles of two components as in the positive electrode active material disclosed in Patent Document 1, there is a problem that it is essentially difficult to improve the energy density.
[0014] It is believed that this is because: the thermal stability of the positive electrode active material for lithium ion secondary batteries is reduced, and the structure of the positive electrode active material for lithium ion secondary batteries becomes unstable. When in a charged state, the oxygen released from the positive electrode active material for lithium ion secondary batteries reacts with organic matter contained in the electrolyte, etc. Therefore, it is required to suppress the release of oxygen in a charged state.
[0015] Therefore, in view of the above-mentioned problems of the prior art, an object of one aspect of the present invention is to provide a positive electrode active material for a lithium ion secondary battery in which oxygen release in a charged state is suppressed.
[0016] Methods for solving problems
[0017] In order to solve the above-mentioned problems, according to one embodiment of the present invention, there is provided a positive electrode active material for a lithium ion secondary battery, which is a positive electrode active material for a lithium ion secondary battery containing a lithium metal composite oxide.
[0018] The lithium metal composite oxide contains lithium (Li), nickel (Ni), cobalt (Co) and element M (M) in a ratio of Li:Ni:Co:M=1+a:1-xy:x:y (wherein -0.05≤a≤0.50, 0≤x≤0.35, 0≤y≤0.35, and the element M is at least one element selected from Mg, Ca, Al, Si, Fe, Cr, Mn, V, Mo, W, Nb, Ti, Zr, and Ta) in a ratio of molar mass.
[0019] At 4.3V (vs.Li +When the cross section of the lithium metal composite oxide particle is subjected to STEM-EELS analysis from the surface toward the center of the particle during charging with a lithium metal composite oxide (Li / Li), the thickness of the oxygen easy-releasing layer is 200 nm or less when the intensity ratio (1st / 2nd) of the peak near 530 eV (1st) and the peak near 545 eV (2nd) at the OK end is 0.9 or less,
[0020] The specific surface area is 0.7m 2 / g above 2.0m 2 / g or less.
[0021] Effects of the Invention
[0022] According to one aspect of the present invention, it is possible to provide a positive electrode active material for a lithium ion secondary battery in which oxygen release in a charged state is suppressed. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a schematic cross-sectional view of a 2032-type button cell specified in battery evaluation.
[0024] Figure 2A 3 is a STEM image showing a cross section of a particle of the lithium metal composite hydroxide obtained in Example 1.
[0025] Figure 2B FIG. 1 is an EELS spectrum of a cross section of a lithium metal composite hydroxide particle obtained in Example 1. FIG.
[0026] Figure 3A 3 is a STEM image showing a cross section of a particle of the lithium metal composite hydroxide obtained in Comparative Example 2.
[0027] Figure 3B FIG. 1 is an EELS spectrum of a particle cross section of the lithium metal composite hydroxide obtained in Comparative Example 2. DETAILED DESCRIPTION
[0028] Hereinafter, the present specific embodiment will be described with reference to the drawings, but the present invention is not limited to the following embodiment, and various modifications and substitutions can be made to the following embodiment without departing from the scope of the present invention.
[0029] [Positive electrode active material for lithium ion secondary batteries]
[0030] The positive electrode active material for lithium ion secondary battery of the present embodiment (hereinafter, also simply described as “positive electrode active material”) can contain a lithium metal composite oxide.
[0031] The lithium metal composite oxide may contain lithium (Li), nickel (Ni), cobalt (Co) and element M (M) in a ratio of Li:Ni:Co:M=1+a:1-xy:x:y in terms of the amount of matter. However, a, x, and y in the above formula preferably satisfy -0.05≤a≤0.50, 0≤x≤0.35, and 0≤y≤0.35, respectively. In addition, element M may be at least one element selected from Mg, Ca, Al, Si, Fe, Cr, Mn, V, Mo, W, Nb, Ti, Zr, and Ta.
[0032] Moreover, it is possible to make the + When the cross section of a lithium metal composite oxide particle is subjected to STEM-EELS analysis from the surface toward the center of the particle during charging with a lithium metal composite oxide (Li / Li), the thickness of the oxygen easy-releasing layer is 200 nm or less when the intensity ratio (1st / 2nd) of the peak near 530 eV (1st) and the peak near 545 eV (2nd) at the OK end is 0.9 or less. In addition, the specific surface area can be 0.7 m 2 / g above 2.0m 2 / g or less.
[0033] The inventors of the present invention have conducted intensive studies on the influence of powder properties of a lithium metal composite oxide used as a positive electrode active material in order to produce a positive electrode active material that suppresses oxygen release in a charged state and on the positive electrode resistance of a battery.
[0034] As a result, it was found that an oxygen-releasing layer that easily releases oxygen is sometimes formed on the particle surface of the lithium metal composite oxide during charging, and there is a correlation between the thickness of the oxygen-releasing layer and the amount of oxygen released from the positive electrode active material during charging. Further, it was found that the oxygen-releasing layer is a layer generated by particles from which Li is excessively released due to the unevenness of the electrochemical reaction between the particles in the electrode, so the particle characteristics are controlled so that the specific surface area is within a specified range, and the electrochemical reaction occurs uniformly, thereby suppressing oxygen release and obtaining high thermal stability. Therefore, it was found that by suppressing the thickness of the oxygen-releasing layer on the particle surface of the lithium metal composite oxide contained, a positive electrode active material with specified particle characteristics is prepared, thereby suppressing oxygen release in the charged state, improving thermal stability, and completing the invention.
[0035] The positive electrode active material of the present embodiment may contain a lithium metal composite oxide as described above. The positive electrode active material of the present embodiment may also be composed of a lithium metal composite oxide.
[0036] The lithium metal composite oxide may contain lithium (Li), nickel (Ni), cobalt (Co) and element M (M) in a ratio of Li:Ni:Co:M=1+a:1-xy:x:y in terms of the amount of matter. In the above formula, a, x and y preferably satisfy -0.05≤a≤0.50, 0≤x≤0.35 and 0≤y≤0.35, respectively.
[0037] The value of a indicating the excess amount of lithium (Li) is preferably -0.05 to 0.50, more preferably 0 to 0.20, and even more preferably 0 to 0.10, as described above.
[0038] By making a be between -0.05 and 0.50, the output characteristics and battery capacity of the secondary battery using the positive electrode active material containing the lithium metal composite oxide as the positive electrode material can be improved. In contrast, when the value of a is less than -0.05, the positive electrode resistance of the secondary battery involved becomes larger, so there is a concern that the output characteristics cannot be fully improved. On the other hand, if it exceeds 0.50, there is a concern that the initial discharge capacity decreases and the positive electrode resistance increases.
[0039] As described above, x indicating the cobalt content can be set to 0 or more and 0.35 or less. However, particularly when the nickel content is increased, x can be set to, for example, 0 or more and 0.20 or less, and the content can be selected so that the cobalt ratio decreases.
[0040] When the positive electrode active material containing the lithium metal composite oxide is used in a secondary battery, in order to further improve the durability and output characteristics of the secondary battery, in addition to the above-mentioned lithium, nickel, and cobalt, an element M as an additive element may be contained. As the element M, one or more selected from magnesium (Mg), calcium (Ca), aluminum (Al), silicon (Si), iron (Fe), chromium (Cr), manganese (Mn), vanadium (V), molybdenum (Mo), tungsten (W), niobium (Nb), titanium (Ti), zirconium (Zr), and tantalum (Ta) can be used.
[0041] The value of y representing the content of element M is preferably 0 or more and 0.35 or less, more preferably 0 or more and 0.10 or less, and further preferably 0.001 or more and 0.05 or less. By setting the value of y to 0.35 or less, the metal element that contributes to the Redox reaction can be sufficiently ensured, and the battery capacity can be sufficiently improved. In addition, element M may not be added, so it can be set to 0 or more.
[0042] The element M may be uniformly dispersed inside the secondary particles of the lithium metal composite oxide contained in the positive electrode active material, or may cover the surface of the secondary particles of the lithium metal composite oxide. Furthermore, the element M may be uniformly dispersed inside the secondary particles of the lithium metal composite oxide, and then the surface of the secondary particles of the lithium metal composite oxide may be covered. That is, it is preferred that the element M is uniformly distributed inside the secondary particles of the lithium metal composite oxide, or uniformly covers the surface of the secondary particles, or both.
[0043] In addition, no matter how the element M is contained in the lithium metal composite oxide, it is preferable to control the amount of the element M added so as to satisfy the above-described range.
[0044] The lithium metal composite oxide of this embodiment can be, for example, 1+a Ni 1-x-y Co x M y O 2+z In addition, since a, x, and y in the above general formula have been described, their description is omitted here. In addition, z is preferably, for example, 0≤z≤0.10.
[0045] The positive electrode active material of the present embodiment may include primary particles and secondary particles formed by aggregation of a plurality of primary particles. The positive electrode active material of the present embodiment may also be composed of secondary particles formed by aggregation of a plurality of primary particles.
[0046] In addition, the primary particles and secondary particles can be, for example, particles of lithium metal composite oxide.
[0047] Furthermore, the positive electrode active material of this embodiment is prepared by 4.3V (vs. Li + The thickness of the oxygen easy-releasing layer of the lithium metal composite oxide particles obtained by STEM-EELS (Scanning Transmission Electron Microscope-Electron Energy-Loss Spectroscopy) observation during charging of lithium metal composite oxide (Li / Li) is preferably 200 nm or less.
[0048] As described above, according to the research of the inventors of the present invention, an oxygen-releasing layer is sometimes formed on the surface of the lithium metal composite oxide particles during charging, and there is a correlation between the thickness of the oxygen-releasing layer and the amount of oxygen released from the positive electrode active material during charging. +When the lithium metal composite oxide particles during charging of lithium-ion battery (Li) are observed by STEM-EELS, when the thickness of the oxygen easy-releasing layer is 200 nm or less, a positive electrode active material that fully suppresses the oxygen release amount from the positive electrode active material during charging can be prepared. That is, a positive electrode active material with excellent thermal stability can be prepared.
[0049] In addition, 4.3V (vs.Li + When the lithium metal composite oxide particles are observed by STEM-EELS during charging of lithium metal composite oxide (Li / Li), the thickness of the oxygen easy-releasing layer is more preferably 100 nm or less, and further preferably 50 nm or less.
[0050] The thickness of the oxygen-releasing layer on the surface of the particles of the lithium metal composite oxide during charging can be evaluated by observation using STEM-EELS. Specifically, using STEM-EELS, the secondary particle size is smaller than the volume average particle size of the positive electrode active material, and the oxygen-releasing layer is easy to observe, for example, the secondary particle size of the lithium metal composite oxide particles is less than 2 / 3 of the volume average particle size of the positive electrode active material, and the cross-sectional structure is observed. Moreover, it is possible to measure the spectrum using EELS at a certain interval along the diameter direction from the particle surface toward the center on the cross section of the particle, and measure the peak (1st) near the OK end 530eV and the peak near 545eV (2nd) The intensity ratio (1st / 2nd) becomes less than 0.9, and the thickness of the oxygen-releasing layer from the particle surface is obtained.
[0051] This is because the peak (1st) near 530eV represents LiNiO2 or a compound using LiNiO2 as a skeleton, while the peak (2nd) near 545eV represents NiO. Moreover, according to the research of the inventors of the present invention, the oxygen easy-releasing layer whose intensity ratio of the 1st peak to the intensity of the 2nd peak representing NiO is 0.9 or less becomes a layer with low oxygen retention capacity, and by making the thickness of the layer involved 200nm or less, the amount of oxygen released can be suppressed even when the temperature is increased, thereby improving thermal stability.
[0052] The specific surface area of the positive electrode active material of this embodiment is preferably 0.7 m 2 / g above 2.0m 2 / g or less, more preferably 0.8m 2 / g above 1.7m 2 / g or less.
[0053] By making the specific surface area of the positive electrode active material within the above range, the contact area with the electrolyte can be fully increased, and the reaction field where the intercalation reaction of Li ions occurs can be widened. Therefore, the excess separation of local lithium can be reduced, especially the release of oxygen can be suppressed, and the thermal stability can be improved.
[0054] Specifically, by making the specific surface area of the positive electrode active material 0.7 m 2 / g or more, thereby being able to fully ensure the electrochemical reaction field, suppress the generation of particles where lithium is locally released and increase the thermal stability. In addition, by making the specific surface area of the positive electrode active material 2.0m 2 / g or less, it is possible to suppress excessive increase in reactivity with the electrolyte and, in particular, to improve thermal stability.
[0055] The specific surface area of the positive electrode active material can be measured by, for example, the BET method using nitrogen adsorption.
[0056] The particle size of the particles contained in the positive electrode active material of this embodiment is not particularly limited. In the particle size distribution using the laser diffraction scattering method, the volume average particle size (MV) is preferably 5 μm to 20 μm, more preferably 7 μm to 20 μm, and further preferably 7 μm to 15 μm.
[0057] When the volume average particle size (MV) of the positive electrode active material is within the above range, not only can the battery capacity per unit volume of a secondary battery using the positive electrode active material be increased, but also the thermal stability and output characteristics can be particularly improved.
[0058] For example, by making the volume average particle size (MV) be 5 μm or more, the filling property of the positive electrode active material can be improved, and the battery capacity per unit volume can be increased. In addition, by making the volume average particle size (MV) be 20 μm or less, the reaction area of the positive electrode active material can be increased, and the interface with the electrolyte can be increased, so the output characteristics can be improved.
[0059] The volume average particle size (MV) of the positive electrode active material refers to a volume-based average particle size (MV), and can be determined, for example, from a volume integrated value measured using a laser diffraction scattering particle size analyzer.
[0060] In addition, the positive electrode active material of the present embodiment preferably has a ratio [(d90-d10) / volume average particle size] which is an index showing the width of the particle size distribution of 0.80 or more, more preferably 0.85 or more, and even more preferably 0.90 or more.
[0061] By setting the above index to 0.80 or more, the positive electrode active material can be composed of particles having a wide particle size distribution. Such a positive electrode active material has excellent packing properties, and a secondary battery using the positive electrode active material has excellent energy density.
[0062] The upper limit of the above index is not particularly limited, but is, for example, preferably 1.25 or less, more preferably 1.20 or less, and further preferably 1.00 or less.
[0063] In addition to the above-described specific surface area of the positive electrode active material, by setting the width of the particle size distribution to the above-mentioned range, it is possible to suppress the formation of an oxygen easy-releasing layer during charge in particular.
[0064] In addition, d10 represents the cumulative 10% particle diameter, which represents the particle diameter at which the volume cumulative value in the particle size distribution obtained by laser diffraction scattering method is 10%. d90 represents the cumulative 90% particle diameter, which represents the particle diameter at which the volume cumulative value in the particle size distribution obtained by laser diffraction scattering method is 90%.
[0065] In addition, the tap density of the positive electrode active material of the present embodiment is not particularly limited, and can be arbitrarily selected according to the required performance, etc. However, in order to extend the use time of portable electronic devices and the driving distance of electric vehicles, the high capacity of lithium ion secondary batteries has become an important issue. On the other hand, the thickness of the electrode of the lithium ion secondary battery is required to be about several microns due to the filling and electronic conductivity of the entire battery. Therefore, it is required not only to use a high-capacity material as the positive electrode active material, but also to improve the fillability of the positive electrode active material, to achieve the high capacity of the lithium ion secondary battery as a whole.
[0066] From this viewpoint, in the positive electrode active material of this embodiment, the tap density, which is an index of filling property, is preferably 2.0 g / cm 3 More preferably, 2.2 g / cm 3 above.
[0067] By making the tap density 2.0 g / cm 3 On the other hand, there is no particular restriction on the upper limit of the tap density, and the upper limit under normal manufacturing conditions is 3.0 g / cm 3 So it is preferably 3.0g / cm 3 the following.
[0068] The tap density refers to the bulk density of a sample powder collected in a container and shaken 100 times based on JIS Z 2504 (2012), and can be measured using an oscillating specific gravity meter.
[0069] [Method for producing positive electrode active material for lithium ion secondary battery]
[0070] Next, a method for producing the positive electrode active material for a lithium ion secondary battery according to the present embodiment will be described.
[0071] The method for producing a positive electrode active material for a lithium ion secondary battery according to the present embodiment (hereinafter, also simply referred to as “a method for producing a positive electrode active material”) can include the following steps.
[0072] The heat treatment step is to heat-treat the metal composite hydroxide at 105° C. to 700° C. to obtain a heat-treated metal composite compound.
[0073] A mixing step of mixing the heat-treated metal composite compound with a lithium compound to form a lithium mixture.
[0074] The calcining step is to calcine the lithium mixture formed in the mixing step in an oxidizing atmosphere at a temperature of 650° C. to 900° C.
[0075] In addition, the metal composite hydroxide can contain nickel (Ni), cobalt (Co) and element M (M) in a ratio of Ni:Co:M=1-xy:x:y in terms of the amount of substance. However, x and y in the above formula preferably satisfy 0≤x≤0.35 and 0≤y≤0.35. In addition, element M can be at least one element selected from Mg, Ca, Al, Si, Fe, Cr, Mn, V, Mo, W, Nb, Ti, Zr, and Ta.
[0076] In addition, the specific surface area of the positive electrode active material obtained after the calcination step can be set to 0.7 m 2 / g above 2.0m 2 / g or less.
[0077] Hereinafter, the manufacturing method of the positive electrode active material for lithium ion secondary battery of this embodiment is described in detail in each process. In addition, the manufacturing method of the positive electrode active material of this embodiment can manufacture the positive electrode active material already described. Therefore, for the matters already described, part of the description is omitted.
[0078] (1) Heat treatment process
[0079] The method for manufacturing the positive electrode active material of the present embodiment can include a heat treatment step of heat-treating the metal composite hydroxide to obtain a heat-treated metal composite compound. Here, the heat-treated metal composite compound obtained by the heat treatment step includes not only the metal composite hydroxide from which the remaining water is removed in the heat treatment step, but also the metal composite oxide converted into an oxide by the heat treatment step, and a mixture thereof.
[0080] The heat treatment conditions in the heat treatment step are not particularly limited. For example, it is preferred that the metal composite hydroxide be heated to 105° C. or higher and 700° C. or lower for heat treatment.
[0081] By performing heat treatment at the above-mentioned temperature, the residual water contained in the metal composite hydroxide can be reduced and removed, and the residual water until the calcination process is reduced to a certain amount. Therefore, the deviation of the composition of the obtained positive electrode active material can be suppressed. In addition, by implementing this heat treatment process, the calcination temperature in the calcination process described later is further set to a specified range, so that the specific surface area of the positive electrode active material obtained after the calcination process can be easily adjusted to a desired range.
[0082] As described above, by heat treatment at 105°C or above, the residual water in the metal composite hydroxide is fully removed, and in particular, the deviation of the composition of the positive electrode active material obtained after the calcination process can be suppressed. However, even if the heat treatment temperature exceeds 700°C, the effect is not greatly different. From the perspective of reducing costs, it is preferably below 700°C.
[0083] In addition, in the heat treatment process, as long as the water is removed to the extent that the ratio of the number of atoms of each metal component and the number of atoms of Li in the positive electrode active material obtained after the sintering process does not produce deviation, it is not necessarily necessary to convert all metal composite hydroxides into oxides. However, in order to reduce the deviation of the ratio of the number of atoms of each metal component and the number of atoms of Li, it is preferably heat-treated at 400° C. or above to convert all metal composite hydroxides into metal composite oxides.
[0084] Furthermore, the above-mentioned variation can be further suppressed by analyzing the metal components contained in the heat-treated metal composite compound under the heat treatment conditions obtained in advance and determining the mixing ratio with the lithium compound.
[0085] The atmosphere for performing the heat treatment is not particularly limited as long as it is a non-reducing atmosphere, and it is preferably performed in an air flow which allows for easy performance.
[0086] The heat treatment time is not particularly limited, but is preferably at least 1 hour, more preferably 5 hours to 15 hours, from the viewpoint of sufficiently removing excess water in the metal composite hydroxide.
[0087] The metal composite hydroxide provided in the heat treatment process can contain nickel (Ni), cobalt (Co) and element M (M) in a ratio of Ni:Co:M=1-xy:x:y in terms of the amount of substance. In addition, x, y, and element M have been described, so the description is omitted here. In addition, x and y can also be selected from the same preferred range as x and y described in the positive electrode active material.
[0088] The metal composite hydroxide can be, for example, of the general formula: Ni 1-x-y Co x M y (OH) 2+α In the above formula, x and y preferably satisfy the ranges described above. In addition, α is preferably -0.2≤α≤0.2, for example.
[0089] (2) Mixing process
[0090] In the mixing step, as described above, the heat-treated metal composite compound and the lithium compound can be mixed to obtain a lithium mixture.
[0091] In the mixing process, the ratio of mixing the heat-treated metal composite compound and the lithium compound is not particularly limited and can be arbitrarily selected according to the composition required by the manufactured positive electrode active material, etc. For example, it is preferred to mix the heat-treated metal composite compound and the lithium compound in such a manner that the ratio (Li / Me) of the sum of the number of atoms of nickel, cobalt and element M other than lithium in the lithium mixture obtained by the mixing process, specifically, the number of atoms of lithium (Li) is greater than 0.95 and less than 1.5. In particular, it is more preferred to mix in such a manner that the above-mentioned Li / Me becomes greater than 1.0 and less than 1.2, and it is further preferred to mix in such a manner that it becomes greater than 1.0 and less than 1.1.
[0092] This is because since Li / Me hardly changes before and after the calcination step, it is preferable to mix the raw materials so that the Li / Me of the lithium mixture obtained in the mixing step becomes the target Li / Me of the positive electrode active material.
[0093] The lithium compound supplied in the mixing step is not particularly limited, but preferably one or more selected from lithium hydroxide, lithium nitrate, and lithium carbonate are used from the perspective of ease of acquisition. In particular, lithium hydroxide or lithium carbonate is more preferably used from the perspective of ease of operation and stability of quality.
[0094] The heat-treated metal composite compound and the lithium compound are preferably fully mixed to a degree that does not produce fine powder. This is because if the mixing is insufficient, sometimes Li / Me will deviate between each particle, and sufficient battery characteristics cannot be obtained. In addition, a common mixer can be used for mixing. For example, a vibration mixer, a Lödige mixer, a Julia mixer, a V-type mixer, etc. can be used.
[0095] (3) Firing process
[0096] The calcining step is a step of calcining the lithium mixture obtained in the mixing step under predetermined conditions to diffuse lithium into the heat-treated metal composite compound to obtain a lithium metal composite oxide.
[0097] In addition, the furnace used in the sintering process is not particularly limited, as long as it is a furnace that can heat the lithium mixture in the atmosphere or oxygen gas flow. However, from the viewpoint of uniformly maintaining the atmosphere in the furnace, it is preferably an electric furnace that does not generate gas, and both intermittent and continuous electric furnaces can be suitable for use. In this regard, the same is true for the furnace used in the heat treatment process already described and the pre-sintering process described later.
[0098] Hereinafter, suitable firing conditions in the firing step will be described.
[0099] (3-1) Firing temperature
[0100] The calcination temperature of the lithium mixture is preferably 650°C to 900°C, more preferably 650°C to 850°C. By setting the calcination temperature to 650°C or higher, lithium can be fully diffused into the heat-treated metal composite compound, and the remaining lithium and unreacted heat-treated metal composite compound can be suppressed. In addition, the crystallinity of the obtained lithium metal composite oxide can be improved, so it is preferred.
[0101] Furthermore, by setting the calcination temperature to 900° C. or lower, it is possible to suppress intense sintering between particles of the lithium metal composite oxide and to suppress abnormal grain growth, thereby suppressing the generation of indeterminate coarse particles.
[0102] Furthermore, by selecting the calcination temperature in the calcination step within the above range, the specific surface area of the obtained positive electrode active material can also be adjusted.
[0103] The temperature increase rate in the calcining step is not particularly limited, but is preferably, for example, 2° C. / minute to 10° C. / minute, and more preferably 3° C. / minute to 8° C. / minute.
[0104] In addition, in the calcining process, it is preferred to temporarily stop the temperature rise at a temperature near the melting point of the lithium compound and maintain it, preferably in this case, maintaining it for more than 1 hour and less than 5 hours, and more preferably maintaining it for more than 2 hours and less than 5 hours. By temporarily stopping the temperature rise at a temperature near the melting point of the lithium compound and maintaining it, the heat-treated metal composite compound and the lithium compound can react more uniformly.
[0105] (3-2) Firing time
[0106] In the calcination time, the holding time at the above-mentioned calcination temperature is also not particularly limited, for example, preferably more than 2 hours, more preferably more than 4 hours. By making the holding time at the calcination temperature in the calcination temperature more than 2 hours, lithium can be fully diffused into the metal composite oxide, and the remaining lithium and unreacted metal composite oxide are suppressed. In addition, the crystallinity of the obtained lithium metal composite oxide can be improved, so it is preferred.
[0107] The upper limit of the calcination time is not particularly limited, but is preferably 48 hours or less from the viewpoint of productivity.
[0108] (3-3) Cooling rate
[0109] In addition, after the above-mentioned holding at the firing temperature is completed, the cooling rate from the firing temperature is not particularly limited. For example, the cooling rate from the firing temperature to 200°C is preferably 2°C / min to 10°C / min, and more preferably 3°C / min to 7°C / min. By making the cooling rate within the above range, it is possible to ensure productivity while more reliably preventing equipment such as saggers from being damaged due to rapid cooling.
[0110] (3-4) Firing atmosphere
[0111] The atmosphere during firing is preferably an oxidizing atmosphere, and more preferably an atmosphere in which the oxygen concentration is more than 18% by volume and less than 100% by volume. This is because by making the oxygen concentration more than 18% by volume, the crystallinity of the obtained lithium metal composite oxide can be particularly improved. In addition, the remainder other than oxygen is not particularly limited, and can be set to inert gases such as nitrogen and rare gases. In addition, the remainder other than the oxygen involved can include carbon dioxide, water vapor, etc. Firing is further preferably carried out in, for example, the atmosphere or an oxygen gas stream.
[0112] The method for producing the positive electrode active material of the present embodiment may also have any steps other than the above-mentioned heat treatment step, mixing step, and sintering step. For example, it may also have a sintering step of sintering the lithium mixture before the sintering step, a pulverizing step of pulverizing the obtained lithium metal composite oxide after the sintering step, etc. These arbitrary steps are described below.
[0113] (4) Pre-burning process
[0114] When lithium hydroxide or lithium carbonate is used as the lithium compound, it is preferred that a calcining step of calcining the lithium mixture is performed after the mixing step and before the calcining step.
[0115] The calcination temperature in the calcination step is not particularly limited, but is preferably 350° C. to 800° C., lower than the calcination temperature in the calcination step, and more preferably 450° C. to 780° C.
[0116] By performing the calcination step, lithium can be sufficiently diffused into the heat-treated metal composite compound, and a more uniform lithium metal composite oxide can be obtained.
[0117] The holding time at the calcination temperature is preferably from 1 hour to 10 hours, more preferably from 3 hours to 6 hours.
[0118] The atmosphere in the calcining step is preferably an oxidizing atmosphere, similar to the calcining step, and more preferably an atmosphere having an oxygen concentration of 18 volume % or more and 100 volume % or less.
[0119] (5) Crushing process
[0120] The lithium metal composite oxide obtained by the firing process sometimes produces agglomeration or mild sintering. In such a case, it is preferred to crush the agglomerate or sintered body of the lithium metal composite oxide. Thus, the average particle size, particle size distribution, specific surface area, etc. of the obtained positive electrode active material can be adjusted to a suitable range. In addition, the so-called crushing refers to the operation of applying mechanical energy to the agglomerate formed by multiple secondary particles produced by sintering necking (necking) between secondary particles during firing, so that the secondary particles themselves are separated almost without destruction, and the agglomerate is released.
[0121] As a method of pulverizing, a known method can be used, for example, a pin mill, a hammer mill, etc. can be used. In addition, at this time, it is preferred to adjust the pulverizing force to an appropriate range in a manner not to destroy the secondary particles. In addition, in the pulverizing step, the specific surface area of the obtained positive electrode active material can also be made to be 0.7 m 2 / g above 2.0m 2 By carrying out the heat treatment step, mixing step, and calcining step described so far under the conditions already described, the specific surface area of the positive electrode active material obtained in the pulverization step is set to a predetermined range, thereby, in particular, being able to suppress the thickness of the oxygen easy-releasing layer formed on the charged positive electrode active material obtained.
[0122] [Lithium-ion secondary battery]
[0123] The lithium ion secondary battery (hereinafter also referred to as “secondary battery”) of the present embodiment can include a positive electrode including the positive electrode active material described above.
[0124] Hereinafter, for an example of a configuration of a secondary battery of the present embodiment, each component is described separately. The secondary battery of the present embodiment includes, for example, a positive electrode, a negative electrode and a non-aqueous electrolyte, and is composed of the same components as a general lithium-ion secondary battery. In addition, the embodiments described below are merely illustrative, and the lithium-ion secondary battery of the present embodiment can be represented by the following embodiments, based on the knowledge of those skilled in the art, in a manner that implements various changes and improvements. In addition, the secondary battery is not particularly limited in its use.
[0125] (positive electrode)
[0126] The positive electrode included in the secondary battery of this embodiment can include the positive electrode active material described above.
[0127] An example of a method for manufacturing a positive electrode is described below. First, the positive electrode active material (powdered), conductive material and binder (adhesive) described above can be mixed to form a positive electrode composite material, and a solvent for purposes such as activated carbon and viscosity adjustment can be further added as needed, and the mixture is kneaded to prepare a positive electrode composite material paste.
[0128] The mixing ratio of each material in the positive electrode composite material becomes the factor that determines the performance of the lithium ion secondary battery, so it can be adjusted according to the purpose. The mixing ratio of the material can be set to the same as the positive electrode of the known lithium ion secondary battery, for example, when the total mass of the solid component of the positive electrode composite material excluding the solvent is set to 100 mass %, the positive electrode active material can be contained in a ratio of 60 mass % to 95 mass %, a conductive material of 1 mass % to 20 mass %, and an adhesive of 1 mass % to 20 mass %.
[0129] The obtained positive electrode composite material paste is applied to the surface of a current collector made of aluminum foil, for example, and dried to disperse the solvent to produce a sheet-like positive electrode. It is also possible to pressurize by roller pressing, etc., which can increase the electrode density, as required. The sheet-like positive electrode obtained by such operation can be cut into appropriate sizes according to the target battery, etc., for the production of the battery.
[0130] As the conductive material, for example, graphite (natural graphite, artificial graphite, expanded graphite, etc.), acetylene black, Ketjen Black (registered trademark), or other carbon black-based materials can be used.
[0131] As the binder (adhesive), since it plays the role of connecting and fixing the active material particles, for example, one or more selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), fluororubber, ethylene propylene diene rubber, styrene butadiene, cellulose resin and polyacrylic acid can be used.
[0132] It is also possible to disperse the positive electrode active material, the conductive material, etc. as needed, and add the solvent that dissolves the binder to the positive electrode composite material. As the solvent, specifically, organic solvents such as N-methyl-2-pyrrolidone can be used. In addition, the positive electrode composite material can also be added with activated carbon in order to increase the double electric layer capacity.
[0133] The method for producing the positive electrode is not limited to the above-mentioned method, and other methods may be used. For example, the positive electrode composite material may be press-formed and then dried in a vacuum atmosphere.
[0134] (negative electrode)
[0135] The negative electrode can use metallic lithium, lithium alloy, etc. In addition, the negative electrode can be a negative electrode active material that can absorb and release lithium ions, mixed with a binder, and a negative electrode composite material made into a paste by adding a suitable solvent is applied to the surface of a metal foil collector such as copper, dried, and compressed to increase the electrode density as needed.
[0136] As the negative electrode active material, for example, natural graphite, artificial graphite, sintered organic compounds such as phenolic resin and powdered carbon materials such as coke can be used. In this case, as the negative electrode binder, similar to the positive electrode, fluorine-containing resins such as PVDF can be used, and as the solvent for dispersing these active materials and the binder, organic solvents such as N-methyl-2-pyrrolidone can be used.
[0137] (Diaphragm)
[0138] The positive electrode and the negative electrode may be arranged with a separator interposed therebetween as required. The separator separates the positive electrode and the negative electrode and retains the electrolyte, and a known separator may be used, for example, a thin film such as polyethylene or polypropylene having a large number of minute pores may be used.
[0139] (Non-aqueous electrolyte)
[0140] As the non-aqueous electrolyte, for example, a non-aqueous electrolytic solution can be used.
[0141] As the non-aqueous electrolyte, for example, a non-aqueous electrolyte in which a lithium salt as a supporting salt is dissolved in an organic solvent can be used. In addition, as the non-aqueous electrolyte, a non-aqueous electrolyte in which a lithium salt is dissolved in an ionic liquid can be used. In addition, the so-called ionic liquid refers to a salt that is composed of cations and anions other than lithium ions and is liquid even at room temperature.
[0142] As the organic solvent, one selected from cyclic carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate and trifluoropropylene carbonate, chain carbonates such as diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate and dipropyl carbonate, ether compounds such as tetrahydrofuran, 2-methyltetrahydrofuran and dimethoxyethane, sulfur compounds such as ethyl methyl sulfone and butane sultone, phosphorus compounds such as triethyl phosphate and trioctyl phosphate, etc. can be used alone, or two or more selected from them can be used in combination.
[0143] As the supporting salt, LiPF6, LiBF4, LiClO4, LiAsF6, LiN(CF3SO2)2 and complex salts thereof can be used. Furthermore, the non-aqueous electrolyte may contain a radical scavenger, a surfactant, a flame retardant and the like.
[0144] In addition, as the non-aqueous electrolyte, a solid electrolyte can be used. The solid electrolyte has the property of being able to withstand high voltage. Examples of the solid electrolyte include inorganic solid electrolytes and organic solid electrolytes.
[0145] Examples of the inorganic solid electrolyte include oxide-based solid electrolytes and sulfide-based solid electrolytes.
[0146] The oxide-based solid electrolyte is not particularly limited, and can be suitably used, for example, an oxide-based solid electrolyte containing oxygen (O) and having lithium ion conductivity and electronic insulation. As the oxide-based solid electrolyte, for example, lithium phosphate (Li3PO4), Li3PO4N X 、LiBO2N X , LiNbO3, LiTaO3, Li2SiO3, Li4SiO4-Li3PO4, Li4SiO4-Li3VO4, Li2O-B2O3-P2O5, Li2O-SiO2, Li2O-B2O3-ZnO, Li 1+X Al X Ti 2-X (PO4)3(0≤X≤1), Li 1+X Al X Ge 2-X (PO4)3(0≤X≤1), LiTi2(PO4)3, Li 3X La 2 / 3-X TiO3(0≤X≤2 / 3), Li5La3Ta2O 12 、Li7La3Zr2O 12 、Li6BaLa2Ta2O 12 , Li 3.6 Si 0.6 P 0.4 One or more of O4, etc.
[0147] As sulfide-based solid electrolytes, there are no particular limitations, and for example, sulfide-based solid electrolytes containing sulfur (S) and having lithium ion conductivity and electronic insulation can be suitably used. As sulfide-based solid electrolytes, for example, Li2S-P2S5, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2S-B2S3, Li3PO4-Li2S-Si2S, Li3PO4-Li2S-SiS2, LiPO4-Li2S-SiS, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, etc. can be cited.
[0148] In addition, as the inorganic solid electrolyte, an inorganic solid electrolyte other than the above may be used, and for example, one or more selected from Li3N, LiI, Li3N-LiI-LiOH, etc. can be used.
[0149] The organic solid electrolyte is not particularly limited as long as it is a polymer compound showing ion conductivity, and for example, polyethylene oxide, polypropylene oxide, copolymers thereof, etc. can be used. In addition, the organic solid electrolyte may contain a supporting salt (lithium salt).
[0150] (Shape and structure of secondary battery)
[0151] The lithium-ion secondary battery of the present embodiment described above can adopt various shapes such as cylindrical and stacked. In the case of adopting any shape, if the secondary battery of the present embodiment uses a non-aqueous electrolyte as a non-aqueous electrolyte, the positive electrode and the negative electrode can be stacked through a separator to form an electrode body, the non-aqueous electrolyte is impregnated in the obtained electrode body, and the positive electrode collector is connected to the positive terminal connected to the outside, and the negative electrode collector is connected to the negative terminal connected to the outside using a collector lead, etc., to form a structure sealed in the battery case.
[0152] In addition, as described above, the secondary battery of this embodiment is not limited to the method of using a non-aqueous electrolyte as a non-aqueous electrolyte, and can also use a secondary battery using a solid non-aqueous electrolyte, i.e., a fully solid battery. In the case of a fully solid battery, the composition other than the positive electrode active material can be changed as needed.
[0153] The secondary battery of this embodiment has a positive electrode using the positive electrode active material of this embodiment as a positive electrode material, and therefore has excellent thermal stability. Moreover, it can be said that it has excellent thermal stability even compared with a conventional secondary battery using a positive electrode active material formed of lithium nickel composite oxide particles.
[0154] As described above, the secondary battery of this embodiment has excellent thermal stability, and further has excellent battery capacity, output characteristics and cycle characteristics, and can be used for small portable electronic devices that require these characteristics at a high level, such as power supplies for notebook personal computers, mobile phones, etc. In addition, the secondary battery of this embodiment is also excellent in safety, and can not only be miniaturized and high-output, but also simplify expensive protection circuits, so it can also be used as a power supply for transportation equipment with limited mounting space.
[0155] Example
[0156] Hereinafter, the present invention will be further described in detail by way of examples and comparative examples, but the present invention is not limited to any of these examples. In addition, in the following examples and comparative examples, unless otherwise specified, each sample of a special grade reagent manufactured by Wako Pure Chemical Industries, Ltd. is used for the preparation of the positive electrode active material.
[0157] [Example 1]
[0158] (1) Preparation of positive electrode active material
[0159] The general formula with Ni as the main component: Ni 0.90 Co 0.07 Al 0.03 The metal composite hydroxide represented by (OH)2 was heat-treated at 600°C for 5 hours in an air flow (oxygen concentration: 21 volume %) (heat-treatment step). Thus, as a heat-treated metal composite compound, a general formula: Ni 0.90 Co 0.07 Al 0.03 The metal composite oxide represented by O.
[0160] Next, the metal composite oxide obtained by the heat treatment step and lithium hydroxide are weighed and fully mixed in such a manner that Li / Me, which is the ratio of the number of lithium atoms (Li) to the number of metal atoms other than lithium (Me) in the obtained lithium mixture, becomes 1.01, thereby obtaining a lithium mixture (mixing step).
[0161] A vibration mixer device (TURBULA Type T2C manufactured by Willy A. Bachofen (WAB)) was used for mixing.
[0162] The lithium mixture obtained in the mixing step was calcined in an oxygen (oxygen concentration: 100 volume %) gas flow at a heating rate of 3°C / min to 750°C and maintained at 750°C for 6 hours. After calcination, the mixture was cooled to room temperature at a cooling rate of about 4°C / min (calcination step).
[0163] After the calcination step, the obtained positive electrode active material is aggregated or slightly sintered. Therefore, the positive electrode active material is pulverized to adjust the average particle size and particle size distribution (pulverization step).
[0164] (2) Evaluation of positive electrode active materials
[0165] (2-1) Composition
[0166] By analyzing using an ICP emission spectrometer (manufactured by Shimadzu Corporation, ICPE-9000), it was confirmed that the obtained positive electrode active material was composed of the general formula: Li 1.01 Ni 0.90 Co 0.07 Al 0.03 The lithium metal composite oxide shown in O2 is formed. The cross section of the secondary particles of the lithium metal composite oxide contained in the positive electrode active material was analyzed by SEM-EDS, and the results confirmed that Al was uniformly dispersed in the secondary particles. The same applies to the following other examples.
[0167] (2-2) Volume average particle size and particle size distribution
[0168] The volume average particle size (MV) of the positive electrode active material was measured using a laser diffraction scattering particle size analyzer (MICROTRAC BEL Co., Ltd., MICROTRAC MT3300EXII), and d10 and d90 were measured to calculate [(d90-d10) / volume average particle size] as an indicator of the width of the particle size distribution.
[0169] As a result, it was confirmed that the volume average particle size (MV) was 11.4 μm and [(d90-d10) / volume average particle size] was 0.93.
[0170] (2-3) Specific surface area and tap density
[0171] The specific surface area was measured by a flow gas adsorption specific surface area measuring device (Macsorb 1200 series, manufactured by Mountech Co., Ltd.), and the tap density was measured by a tap compaction device (KRS-406, manufactured by Kurachi Scientific Instruments Co., Ltd.). The specific surface area was confirmed to be 1.38 m 2 / g, tap density is 2.85g / cm 3 .
[0172] The specific surface area was measured by the BET method using nitrogen adsorption. The tap density was determined by measuring the bulk density of a sample powder collected in a container and shaken 100 times in accordance with JIS Z2504 (2012).
[0173] (3) Fabrication of lithium-ion secondary batteries
[0174] The obtained positive electrode active material was used to prepare a 2032-type button battery.
[0175] use Figure 1 , the structure of the button battery produced is explained. Figure 1 A schematic diagram showing the cross-sectional structure of a button battery.
[0176] like Figure 1 As shown, the button battery 10 is composed of a housing 11 and an electrode 12 accommodated in the housing 11 .
[0177] The shell 11 includes: a positive electrode can 111 which is hollow and has an open end, and a negative electrode can 112 which is arranged at the opening of the positive electrode can 111. The negative electrode can 112 is arranged at the opening of the positive electrode can 111, and a space for accommodating the electrode 12 is formed between the negative electrode can 112 and the positive electrode can 111.
[0178] The electrode 12 includes a positive electrode 121 , a separator 122 , and a negative electrode 123 , which are stacked in this order and housed in the case 11 so that the positive electrode 121 contacts the inner surface of the positive electrode can 111 and the negative electrode 123 contacts the inner surface of the negative electrode can 112 .
[0179] The housing 11 is provided with a gasket 113, and is fixed by the gasket 113 so as to maintain an electrical insulation state between the positive electrode can 111 and the negative electrode can 112. The gasket 113 also has the function of sealing the gap between the positive electrode can 111 and the negative electrode can 112, and blocking the inside and outside of the housing 11 in an airtight and liquid-tight manner.
[0180] The button battery 10 is manufactured as follows.
[0181] First, 52.5 mg of positive electrode active material, 15 mg of acetylene black, and 7.5 mg of PTFE were mixed, pressed at a pressure of 100 MPa into a shape with a diameter of 11 mm and a thickness of 100 μm, and then dried in a vacuum dryer at 120° C. for 12 hours to produce a positive electrode 121 .
[0182] Next, using the positive electrode 121, a 2032-type button cell 10 was made in a glove box with an Ar atmosphere whose dew point was controlled to -80°C. The negative electrode 123 of the 2032-type button cell used a lithium metal with a diameter of 17 mm and a thickness of 1 mm, and the electrolyte used an equal amount of a mixed solution of ethylene carbonate (EC) and diethyl carbonate (DEC) with 1M LiClO4 as a supporting electrolyte (manufactured by Toyama Pharmaceutical Industry Co., Ltd.). In addition, the separator 122 used a polyethylene porous film with a film thickness of 25 μm.
[0183] (4) Evaluation of lithium-ion secondary batteries
[0184] (4-1) Initial discharge capacity
[0185] After making the 2032-type button battery, let it sit for about 24 hours. After the open circuit voltage (OCV) stabilizes, set the current density relative to the positive electrode to 0.1 mA / cm 2 , charging was performed until the cut-off voltage became 4.3V, and after pausing for 1 hour, the discharge capacity when the cut-off voltage became 3.0V was measured, and the above-mentioned charge and discharge test was performed to obtain the initial discharge capacity. The result confirmed that the initial discharge capacity was 214.6mAh / g. In addition, the determination of the initial discharge capacity used a multi-channel voltage / current generator (made by Advantest Co., Ltd., R6741A).
[0186] (4-2) Thermal stability
[0187] The thermal stability of the positive electrode active material is evaluated by quantifying the amount of oxygen released by heating the positive electrode active material to an overcharged state. The above-mentioned 2032-type button cell was made and charged at a CCCV rate of 0.2C (constant current-constant voltage charging) until the cutoff voltage was 4.3V. Then, the button cell was disassembled, and only the positive electrode was carefully removed in a manner that did not cause a short circuit, and it was washed with DMC (dimethyl carbonate) and dried. About 2 mg of the dried positive electrode active material was measured and heated from room temperature to 450°C at a heating rate of 5°C / min using a gas chromatograph mass spectrometer (GCMS, Shimadzu Corporation, QP-2010plus). Helium was used as a carrier gas. The generation behavior of oxygen (m / z=32) generated during heating was measured, and the oxygen generation amount was semi-quantitatively determined from the maximum oxygen generation peak height and peak area obtained, and these were used as evaluation indicators of thermal stability. In addition, the semi-quantitative value of the oxygen generation amount was calculated by injecting pure oxygen as a standard sample into the GCMS and extrapolating the standard curve obtained from the measurement results. Then, the mass ratio of oxygen gas to helium gas as a carrier gas was calculated as the oxygen release amount. As a result, an oxygen release amount of 7.8 mass % was confirmed.
[0188] (4-3) Thickness of oxygen-releasing layer
[0189] The evaluation of the thickness of the oxygen easily releasable layer in the positive electrode active material particles during charging is carried out in the same manner as in the thermal stability test. After charging the above-mentioned 2032 type button battery, the button battery is disassembled, and only the positive electrode is taken out in a manner that does not cause a short circuit. The positive electrode is then buried in a resin, and the thickness of the oxygen easily releasable layer is evaluated by using the ELV-2000 elements view as an electron energy loss spectrometer (EELS) equipped with a scanning transmission electron microscope (STEM) (manufactured by Hitachi High-Tech, HD-2300A) in a state where cross-section observation can be performed by focused ion beam processing.
[0190] In addition, when evaluating the thickness of the oxygen easy-releasing layer, lithium metal composite oxide particles whose secondary particle size is less than 2 / 3 of the volume average particle size of the positive electrode active material are selected. Moreover, for the particles, the spectrum is measured by EELS at a certain interval along the diameter direction from the particle surface toward the center, and the thickness of the region where the intensity ratio (1st / 2nd) of the peak (1st) near 530eV at the OK end and the peak (2nd) near 545eV is less than 0.9 is measured, thereby obtaining the thickness of the oxygen easy-releasing layer. In addition, when selecting lithium metal composite oxide particles for evaluating the thickness of the oxygen easy-releasing layer, the diameter of the circle circumscribed with the lithium metal composite oxide particles is set as the secondary particle size of the lithium metal composite oxide particles.
[0191] The STEM observation image and EELS spectrum are shown in Figure 2A , Figure 2B middle.
[0192] from Figure 2A The surface of the particle 21 in the STEM image shown was subjected to EELS analysis at predetermined distances, and the results are shown in FIG. Figure 2B In addition, Figure 2B The numerical values in refer to the distance from the particle surface and represent the EELS spectrum at each position.
[0193] Moreover, by Figure 2B In the EELS spectrum shown, the region where the peak intensity ratio was 0.9 or less was defined as the oxygen easy releasing layer, and the thickness thereof was determined. As a result, the thickness of the oxygen easy releasing layer was 35 nm.
[0194] The results are summarized in Table 1.
[0195] [Example 2]
[0196] So that the specific surface area becomes 1.89m 2The positive electrode active material and secondary battery were obtained and evaluated in the same manner as in Example 1 except that the calcination temperature was 720° C. The results are shown in Table 1.
[0197] [Example 3]
[0198] So that the specific surface area is 0.80m 2 The positive electrode active material and secondary battery were obtained and evaluated in the same manner as in Example 1 except that the calcination temperature was 780° C. The results are shown in Table 1.
[0199] [Comparative Example 1]
[0200] So that the specific surface area is 2.10m 2 The positive electrode active material and secondary battery were obtained and evaluated in the same manner as in Example 1 except that the calcination temperature was 700° C. The results are shown in Table 1.
[0201] [Comparative Example 2]
[0202] So that the specific surface area becomes 0.55m 2 The positive electrode active material and secondary battery were obtained and evaluated in the same manner as in Example 1 except that the calcination temperature was 830° C. The results are shown in Table 1.
[0203] In addition, the STEM observation image and EELS spectrum taken when evaluating the thickness of the oxygen easy-releasing layer are shown in Figure 3A , Figure 3B middle. Figure 3A This shows the STEM observation image. Figure 3B Indicates the EELS spectrum. In addition, even in Figure 3A , Figure 3B In the case shown, it will also Figure 3A The results of EELS analysis at predetermined distances from the surface of the particle 31 in the STEM image shown are shown in FIG. Figure 3B In addition, Figure 3B The numerical values in refer to the distance from the particle surface and represent the EELS spectrum at each position.
[0204] Moreover, by Figure 3B In the EELS spectrum shown, the region where the peak intensity ratio was 0.9 or less was defined as the oxygen easy-releasing layer, and the thickness thereof was determined.
[0205] [Table 1]
[0206]
[0207] From the results shown in Table 1, it can be confirmed that the thickness of the oxygen easy-releasing layer is less than 200 nm and the specific surface area is 0.7 m 2 / g above 2.0m 2 In Examples 1 to 3 with an oxygen release of 15 mass % or less, the oxygen release in the charged state can be sufficiently suppressed. That is, it can be confirmed that a positive electrode active material with excellent thermal stability can be obtained when used in a lithium ion secondary battery.
[0208] The above uses embodiments and examples to illustrate the positive electrode active material for lithium ion secondary batteries, the method for manufacturing the positive electrode active material for lithium ion secondary batteries, and the lithium ion secondary battery, but the present invention is not limited to the above embodiments and examples. Various modifications and changes can be made within the scope of the main purpose of the present invention described in the claims.
[0209] This application claims the priority based on Japanese Patent Application No. 2019-033321 filed with the Japan Patent Office on February 26, 2019, and all the contents of Japanese Patent Application No. 2019-033321 are hereby incorporated by reference into this international application.
Claims
1. A positive electrode active material for a lithium ion secondary battery, which is a positive electrode active material for a lithium ion secondary battery containing a lithium metal composite oxide, The lithium metal composite oxide contains lithium (Li), nickel (Ni), cobalt (Co) and element M (M) in a ratio of Li:Ni:Co:M=1+a:1-xy:x:y in terms of the amount of matter, wherein: -0.05≤a≤0.50, 0≤x≤0.35, 0≤y≤0.35, the element M is at least one element selected from Mg, Ca, Al, Si, Fe, Cr, Mn, V, Mo, W, Nb, Ti, Zr, Ta, At 4.3V (vs.Li + When the cross section of the lithium metal composite oxide particle is subjected to STEM-EELS analysis from the surface toward the center of the particle during charging with lithium metal composite oxide (Li / Li), the thickness of the oxygen easy-releasing layer is 200 nm or less when the intensity ratio (1st / 2nd) of the peak near 530 eV (1st) and the peak near 545 eV (2nd) at the OK end is 0.9 or less, The specific surface area is 0.7m 2 / g above 2.0m 2 / g or less.
2. The positive electrode active material for lithium ion secondary battery according to claim 1, In the particle size distribution determined by a laser diffraction scattering method, the volume average particle size (MV) is 5 μm or more and 20 μm or less.
3. The positive electrode active material for lithium ion secondary battery according to claim 1, The element M is uniformly distributed inside the secondary particles of the lithium metal composite oxide, uniformly covers the surface of the secondary particles, or both.
4. The positive electrode active material for lithium ion secondary battery according to claim 1, wherein [(d90-d10) / volume average particle size] is 0.80 or more.
5. The positive electrode active material for lithium ion secondary battery according to claim 1, having a tap density of 2.0 g / cm 3 above.
6. A method for producing a positive electrode active material for a lithium ion secondary battery, comprising the following steps: a heat treatment step of heat-treating the metal composite hydroxide at a temperature of 105° C. to 700° C. to obtain a heat-treated metal composite compound; a mixing step of mixing the heat-treated metal composite compound with a lithium compound to form a lithium mixture; and a calcining step of calcining the lithium mixture formed in the mixing step in an oxidizing atmosphere at a temperature of 650° C. to 900° C.; The metal composite hydroxide contains nickel (Ni), cobalt (Co) and element M (M) in a ratio of Ni:Co:M=1-xy:x:y in terms of molar ratio, wherein: 0≤x≤0.35, 0≤y≤0.35, the element M is at least one element selected from Mg, Ca, Al, Si, Fe, Cr, Mn, V, Mo, W, Nb, Ti, Zr, and Ta, The specific surface area of the positive electrode active material for lithium ion secondary batteries obtained after the calcination step is 0.7 m 2 / g above 2.0m 2 / g or less. 7 . A lithium ion secondary battery comprising a positive electrode, wherein the positive electrode comprises the positive electrode active material for a lithium ion secondary battery according to claim 1 .
Citation Information
Patent Citations
Positive active material for lithium ion secondary battery using organic electrolyte
JP2008282667A